2019
DOI: 10.1161/jaha.119.012089
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Senescence‐Associated Genes Rb1 and Meis2 in Adult Cardiomyocytes Results in Cell Cycle Reentry and Cardiac Repair Post–Myocardial Infarction

Abstract: BackgroundMyocardial infarction results in a large‐scale cardiomyocyte loss and heart failure due to subsequent pathological remodeling. Whereas zebrafish and neonatal mice have evident cardiomyocyte expansion following injury, adult mammalian cardiomyocytes are principally nonproliferative. Despite historical presumptions of stem cell–mediated cardiac regeneration, numerous recent studies using advanced lineage‐tracing methods demonstrated that the only source of cardiomyocyte renewal originates from the exta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 55 publications
1
52
0
Order By: Relevance
“…Additionally, control injections of hydrogel alone without siRNAs still offered a small degree of cardio-protection, suggesting that intracardiac injection of biological materials following acute myocardial injury may have some small therapeutic benefits. The results of RT-PCR, Western Blot and immunohistochemical analysis together suggested a site-specific induction of CM cell cycle re-entry, keeping the potential low for off-site pathogenic effects such as unintended hyperplasia [23]. Previous attempts to induce re-entry of CMs into the cell cycle have resulted in heart dysfunction.…”
Section: Control Of the Cell Cycle And Rna Interferencementioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, control injections of hydrogel alone without siRNAs still offered a small degree of cardio-protection, suggesting that intracardiac injection of biological materials following acute myocardial injury may have some small therapeutic benefits. The results of RT-PCR, Western Blot and immunohistochemical analysis together suggested a site-specific induction of CM cell cycle re-entry, keeping the potential low for off-site pathogenic effects such as unintended hyperplasia [23]. Previous attempts to induce re-entry of CMs into the cell cycle have resulted in heart dysfunction.…”
Section: Control Of the Cell Cycle And Rna Interferencementioning
confidence: 94%
“…Suppressing cell cycle inhibitors may promote cardiomyocyte proliferation potential. Specifically, downregulating Retinoblastoma1 (Rb1) and Meis Homeobox 2 (Meis2), via small interfering (si)RNA's, induced proliferation of CMs in rats and human cell models and had a positive effect on heart health and improved wound healing [23].…”
Section: Control Of the Cell Cycle And Rna Interferencementioning
confidence: 99%
“…Interestingly, Meis1, a senescence-associated gene, was shown to contribute to the regulation of hematopoietic stem cell metabolism and oxidant stress response, via the transcriptional regulation of hypoxia-inducible factors [ 41 ]. More recent studies revealed that silencing senescence-mediated pathways through inhibition of Meis2 and Rb1 in adult rat cardiomyocytes leads to cardiomyocyte proliferation and cardiac repair upon myocardial infarction [ 42 ]. In addition, FoxO3 was recently reported to mediate cardiac protection from oxidative stress, counteracting cardiac dysfunction, apoptosis and senescence in mice [ 43 ].…”
Section: Cell Senescence Overviewmentioning
confidence: 99%
“…Left ventricular ejection fraction (LVEF) = [(LVEDd 3 − LVESd 3 )/LVEDd 3 ] × 100%; Left ventricular fractional shortening (LVFS) = (LVEDd − LVESd)/LVEDd × 100% 26. LV end-systolic diameter (LVESd) and left ventricular end-diastolic diameter (LVEDd) were calculated using the PVAN analysis software (Millar Instruments).…”
mentioning
confidence: 99%
“…LV end-systolic diameter (LVESd) and left ventricular end-diastolic diameter (LVEDd) were calculated using the PVAN analysis software (Millar Instruments). Left ventricular ejection fraction (LVEF) = [(LVEDd 3 − LVESd 3 )/LVEDd 3 ] × 100%; Left ventricular fractional shortening (LVFS) = (LVEDd − LVESd)/LVEDd × 100% 26.…”
mentioning
confidence: 99%